ACTIVE LEARNING STRATEGIES IN TEACHING CROSS CULTURAL UNDERSTANDING FOR ENGLISH EDUCATION STUDENTS - Ikke Dewi Pratama (Universitas Islam Sultan Agung, 2017)
Cross Cultural Understanding (CCU) is one of required courses in English Language Teaching which aims at connecting language and culture so that language learners can use foreign language appropriately, i.e. appropriate forms of language for appropriate context of situation. However, some obstacles usually occur during the course, for examples: students’ lack of understanding that lead to opinions stating that this is a boring and useless course, and large number of students within a class where lecturer must teach more than 40 students in one class. Considering the importance of CCU course as well as the needs to overcome the problems during this course, this paper proposes some particular teaching strategies to help students in apprehending CCU materials through students’ active participations. Active learning strategies are preferred by means of raising students’ participation and critical thinking so that the class would run more effectively. Other consideration in composing the strategies is to prepare English Education students to be future English language teachers by training their ability in teaching performance as well as connecting language and culture in English Language Teaching (ELT). Keywords: language, culture, strategies, media, ELT